Kontruksi Agama dan Identitas dalam film Cinta Tapi Beda (Analisis Semiotika Film Cinta Tapi Beda) - Fitriana Nur Indah S; Triyono Lukmantoro; Wiwid Noor Rakhmad; M Bayu Widagdo (Interaksi Online, 2015)
Cinta Tapi Beda (2012) that produced by Hestu Saputra and Hanung Bramantyo is one example of the film with the theme of love story of different religions and ethnicities. When released in theaters, December 2012, the film has some pros and cons in the society. Many people found this movie humiliate Minangkabau ethnic group as native of Padang. However, it also had many positive comments because the film is considered to be able to describe the complexity of the love story of different religions and ethnicities in Indonesia. The purpose of this study was to examine how religion and identity construction carried out and communicated in Cinta Tapi Beda (2012). This study uses theory of social construction of Peter L. Berger and Thomas Luckmann in konstrutivis paradigm. The method used in this research is the analysis of semiotic codes of television technical analysis of John Fiske (in Fiske, 1987: 5), which is divided into three levels, namely reality, representation, and ideology.From this research, the findings, which are syntagmatic Islam and Christian is displayed in a simple, not overdone, and obedient to the teachings of his religion. There is a difference between the portrayal of women by men who are Muslims. Munawaroh, Cahyo’s mother and Retno , Cahyo’s sister as Muslim women are described as soft and solehah. They wear veils as evidence of obedient on religion. While the appearance of Cahyo and Fadholi use man’s clothes in general, but they use the peci when pray. They are also described as personal hard and adamant, but still obey to the teachings of religion. As for players who are Christians, the appearance of men and women there was no significant difference. They look like in general. The use of accessories such as necklaces cross only Diana and David.The second finding is based on paradigmatic analysis performed is the myth of religion is presented, which is considered both religion is intolerant of other religions. Other findings is the truth claims made interreligious conflict. Understanding of different religions romantic relationship with all the obstacles. Finally, the attitude of tolerance towards religious pluralism and identity.